Reverse weighted l_p - norm inequalities for convolution type integrals - Nhan, Nguyen Du Vi; Duc, Dinh Thanh; Tuan, Vu Kim (Armenian Journal of Mathematics, 2009)
By using reverse Hölder’s inequalities we obtain reverse weighted L_p norm inequalities for various iterated convolutions.